2010
DOI: 10.1007/s11295-010-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of fruit quality traits in two peach intraspecific populations and importance of maturity date pleiotropic effect

Abstract: Two intraspecific peach breeding populations have been used to conduct a quantitative trait locus (QTL) analysis of fruit quality traits: an F 1 from the cross Bolero (B) x OroA (O) and an F 2 from the cross Contender (C) x Ambra (A). A total of 344 Prunus simple sequence repeats (SSRs) were analyzed in B, O, C, A parents and CxA F 1 hybrid. Eight SSR were mapped for the first time in peach. A multiplex-ready polymerase chain reaction (PCR) protocol has allowed considerable time and cost saving during genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
181
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(210 citation statements)
references
References 59 publications
26
181
2
1
Order By: Relevance
“…The authors indicated that maturity date is a possible Mendelian trait. In the C Â A progeny, the QTL explained 97.5% of the variation in 2007 and 97.7% in 2008 (Eduardo et al, 2011). QTLs controlling maturity date were also detected on LG4 in another peach progeny (Verde et al, 2002), and in almond (Sánchez-Pérez et al, 2007).…”
Section: (Supplementarymentioning
confidence: 86%
See 3 more Smart Citations
“…The authors indicated that maturity date is a possible Mendelian trait. In the C Â A progeny, the QTL explained 97.5% of the variation in 2007 and 97.7% in 2008 (Eduardo et al, 2011). QTLs controlling maturity date were also detected on LG4 in another peach progeny (Verde et al, 2002), and in almond (Sánchez-Pérez et al, 2007).…”
Section: (Supplementarymentioning
confidence: 86%
“…The highest effect was detected for the peach J Â F (EV ¼ 70.4%). A QTL with a major effect was also reported to be located on LG4 in two peach progenies: an F 1 from 'Bolero' and 'OroA' and an F 2 derived from the cross between 'Contender' and 'Ambra' (C Â A) (Eduardo et al, 2011) (Figure 2). The authors indicated that maturity date is a possible Mendelian trait.…”
Section: (Supplementarymentioning
confidence: 95%
See 2 more Smart Citations
“…Another research group (Eduardo et al, 2010) used two progenies from peach crosses to search for QTLs related to fruit quality characteristics. One population was an F 1 population of 'Bolero' (B) × 'OroA' (O) with 129 individuals.…”
Section: Identification Of Qtls and Genesmentioning
confidence: 99%